New understandings of the genetic regulatory relationship between non-coding RNAs and m6A modification - Liu, Songtao; Xiang, Dayong (Frontiers in Genetics, 2023)
One of the most frequent epigenetic modifications of RNA in eukaryotes is N6-methyladenosine (m 6 A), which is mostly present in messenger RNAs. Through the influence of several RNA processing stages, m 6 A modification is a crucial approach for controlling gene expression, especially in cancer progression. It is universally acknowledged that numerous non-coding RNAs (ncRNAs), such as microRNAs, circular RNAs, long non-coding RNAs, and piRNAs, are also significantly affected by m 6 A modification, and the complex genetic regulatory relationship between m 6 A and ncRNAs plays a pivotal role in the development of cancer. The connection between m 6 A modifications and ncRNAs offers an opportunity to explore the oncogene potential regulatory mechanisms and suggests that m 6 A modifications and ncRNAs could be vital biomarkers for multiple cancers. In this review, we discuss the mechanisms of interaction between m 6 A methylation and ncRNAs in cancer, and we also summarize diagnostic and prognostic biomarkers for clinical cancer detection. Furthermore, our article includes some methodologies for identifying m 6 A sites when assessing biomarker potential.